Cranial Vault Fractures in Civilian Head Injury: Clinical and Radiologic Predictors of Seizures and the Fracture Seizure Index: A Prospective Single-Center Observational Cohort Study - Uche, Enoch O.; Okorie, Emeka; Onyia, Ephraim E.; Iloabachie, Izuchukwu; Matthew, Mesi; Amuta, Dubem S.; Mezue, Wilfred C. (Indian Journal of Neurotrauma, 2017)
Study Objectives To determine the risk factors of posttraumatic seizures (PTS) among patients with civilian head injury and skull vault fractures.Methods A 5-year prospective cohort study of patients with skull fractures presenting to our center from March 2013 to February 2017.Results Of 637 patients with traumatic brain injury (TBI), 135 (21.2%) patients sustained calvarial fractures, 91 (72%) were from road traffic accidents (RTAs), and most were young adult males (M:F = 11.6, mean age = 29.1 ± 2.3 years, 95% CL). Linear fractures in 69 patients and depressed fractures in 50 (39.7%) were the common fracture types. Seventy-seven (61.1%) patients had cerebral contusions, 31 (24.6%) had extradural hematoma (EDH), and 21 (16.7%) patients had Glasgow coma scale (GCS) ≤ 8. Twenty-five (18.5%) patients suffered early PTS, and five had late PTS. Among nonfracture patients (n = 361), 31 (8.6%) had seizures. Seizures occurred more in the fracture subgroup (χ2 = 10.1, p < 0.05, df = 1) and earlier (χ2 = 5.9, p = 0.027, df = 1). Fractures and seizures followed a similar trend in occurrence. Among patients with vault fractures, severe head injury, contusions, and intracranial hematoma, the relative risk and odds for early seizures followed a trend predicted by a statistical index—the fracture seizure index (FSI). Late PTS did not show a statistical relationship with early PTS (χ2 = 2.98, df = 1, p > 0.05).Conclusion GCS score ≤8, depressed fracture and multifocal cerebral contusions are predictors of early PTS. Seizure risk associated with fractures and other lesions can be predicted by the FSI.
Keywords: posttraumatic seizures; skull fracture; fracture seizure index